Peran Persepsi Dukungan Organisasi terhadap Kinerja Individu Mahasiswa Magang Tanpa Upah: Mediasi Keterikatan Kerja - Azizah Fatimatuzzahro; Ika Widyarini (Mediapsi, 2026)
Unpaid internship programs have become increasingly common as a cost-saving recruitment strategy, yet their psychological implications for student workers remain underexplored. Drawing on Job Demands-Resources theory, this quantitative correlational study examined whether work engagement mediates the relationship between perceived organizational support (POS) and individual work performance among unpaid interns. Participants were 187 active undergraduate students in Indonesia who were engaged in or had completed unpaid internships lasting 3–6 months during 2024–2025. Data were collected using the Individual Work Performance Questionnaire (IWPQ), Utrecht Work Engagement Scale-9 (UWES-9), and Survey of Perceived Organizational Support-6 (SPOS-6), and analysed using PROCESS Macro Model 4. Results indicated that POS had a significant positive direct effect on individual work performance and a significant positive indirect effect through work engagement (indirect effect = 0.076, 95% Boot CI [0.041, 0.115]). These findings suggest that non-financial forms of organizational support, including mentoring, fair treatment, and constructive feedback, are sufficient to foster work engagement and, in turn, sustain optimal performance among unpaid interns. Program magang tanpa upah semakin banyak digunakan organisasi sebagai strategi rekrutmen berbiaya rendah, namun implikasi psikologisnya bagi mahasiswa peserta magang masih kurang diteliti. Berlandaskan model Job Demands-Resources (JD-R), penelitian kuantitatif korelasional ini mengkaji peran mediasi keterikatan kerja pada hubungan antara persepsi dukungan organisasi dan kinerja individu mahasiswa magang tanpa upah. Partisipan adalah 187 mahasiswa S-1 aktif di Indonesia yang sedang atau pernah mengikuti magang tanpa upah berdurasi 3–6 bulan pada periode 2024–2025. Data dikumpulkan menggunakan Individual Work Performance Questionnaire (IWPQ), Utrecht Work Engagement Scale-9 (UWES-9), dan Survey of Perceived Organizational Support-6 (SPOS-6), serta dianalisis menggunakan PROCESS Macro Model 4. Hasil menunjukkan bahwa persepsi dukungan organisasi berpengaruh positif signifikan secara langsung terhadap kinerja individu, sekaligus berpengaruh positif signifikan secara tidak langsung melalui mediasi keterikatan kerja (indirect effect = 0,076; 95% Boot CI [0,041, 0,115]). Temuan ini mengindikasikan bahwa bentuk dukungan organisasi selain upah finansial, seperti bimbingan mentor, perlakuan adil, dan umpan balik konstruktif, cukup untuk menumbuhkan keterikatan kerja yang pada akhirnya menopang kinerja individu yang optimal pada mahasiswa magang tanpa upah.